The Role of Pancasila to Eradicate the Crime of Corruption - Salsabila, Adelia (Journal of Creativity Student, 2019)
One of the most important problems in Indonesia is the problem of corruption. At present corruption is a very serious crime. And corruption has occurred in many fields. This corruption problem cannot just happen. Of course there are various factors that encourage corruption. And the impact caused by corruption is certainly very detrimental to the Indonesian people. Not only for the Indonesian people but also for all levels of Indonesian society, they also feel the loss of corruption. Various actions have been taken by the government to eradicate corruption cases. However, these acts of corruption are still common in Indonesia. Acts of corruption crimes committed by regional government officials to a higher level. The state apparatus is a group of educated people. But the perpetrators of corruption crimes continue to do bad things even though they know that these actions are inappropriate actions. This shows that the role of Pancasila values has begun to be ignored by the people of Indonesia. Moreover, the ethical and moral values in society that have begun to fade. The challenge in this regard is how Indonesian society can revive roles rather than Pancasila values in an effort to eradicate corruption in the country of Indonesia.